Urbanization in Nepal: Trends, Challenges, and Implications - Deo, Sachindra Kumar; Chaudhary, Deepak (Journey for Sustainable Development and Peace Journal, 2026)
The paper aims to provide a critical analysis of the trends, challenges, and implications of urbanization in Nepal. The study discusses some key issues, including inconsistent definitions of urban areas, poor institutional capacity, unplanned urban expansion, poor infrastructure facilities, and decision-making and political interference through secondary data and qualitative analysis. The urban population has increased dramatically from 17.07% in 2011 to 66.17% in 2021; this increase resulted from administrative reclassification under the federal set-up rather than genuine economic growth or change. The findings indicate that urbanization is predominantly mathematical rather than functional. These results indicate the inefficiencies in urban governance and service delivery. This paper highlights the enhancement of institutional capacity, the implementation of land-use planning, and the alignment of urbanization efforts with economic transformation to foster sustainable development.